Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/ptr.1786
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and free radical scavenging activities ofMisodendrum punctulatum, myzodendrone and structurally related phenols

Abstract: The peroxyl radical scavenging activity of a dry methanol extract of Misodendrum punctulatum was determined by means of luminol-enhanced chemiluminescence assay, allowing to calculate the total reactive antioxidant potential (TRAP) index equal to 239 +/- 26 microm, expressed in Trolox equivalents. The flavan-3-ol catechin (1) and the phenylbutanone derivative myzodendrone (2) were identified through assay-guided fractionation as active metabolites present in the extract, and their structures were elucidated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The antioxidant activity has been attributed to various mechanisms, among which are the prevention of chain initiation, the binding of transition metal ion catalysts, decomposition of peroxides, the prevention of continued hydrogen abstraction, the reductive capacity and radical scavenging. DZ was found to be a free radical scavenger (total reactive antioxidant potential TRAP=229 μM) while zingerone, a hydrogenated product of DZ showed no activity which confirms the activity due to an extended ketone conjugation in DZ (Desmarchelier et al 2005). While, the hydroxyl radical scavenging activity of DZ (ES 15 value=48.36 mM) was reported to be lower than curcumin (25.01 mM) (Nugroho et al 2006).…”
Section: In-vitro Antioxidant Activity Studiesmentioning
confidence: 93%
“…The antioxidant activity has been attributed to various mechanisms, among which are the prevention of chain initiation, the binding of transition metal ion catalysts, decomposition of peroxides, the prevention of continued hydrogen abstraction, the reductive capacity and radical scavenging. DZ was found to be a free radical scavenger (total reactive antioxidant potential TRAP=229 μM) while zingerone, a hydrogenated product of DZ showed no activity which confirms the activity due to an extended ketone conjugation in DZ (Desmarchelier et al 2005). While, the hydroxyl radical scavenging activity of DZ (ES 15 value=48.36 mM) was reported to be lower than curcumin (25.01 mM) (Nugroho et al 2006).…”
Section: In-vitro Antioxidant Activity Studiesmentioning
confidence: 93%
“…Dehydrozingerone (DHZ), isolated from ginger ( Zingiber officinale ), is an unsaturated derivative of the natural product zingerone. DHZ exerts anti‐oxidant , free radical scavenging , and anti‐tumour activities , and also inhibits wound healing and lipid peroxidation . Metabolic roles for DHZ have been proposed, but the molecular mechanisms underlying these effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 1 (7) (Machida & Kikuchi, 1993), p-hydroxyphenyl 6-O-cis-p-Coumaroyl-b-D-glucopyranoside (8) (Machida & Kikuchi, 1993), 4-hydroxybenzoic acid (9) (Rukachaisirikul et al 2010), 4-(methoxymethyl) phenyl-1-Ob-D-glucopyranoside (10) , 3,4-dihydroxyacetophenone (11) (Ruan et al 2011), 3,4-dihytroxy benzaldehyde (12) , p-hytroxy benzaldehyde (13) (Yang et al 2013 ), 3-O-(b-D-glucopyranosyl)-1-(3 0 5 0 -dimethoxy-4-hydroxyphenyl-1-propanone (21) , myzodendrone (22) (Desmarchelier et al 2005) were identified by comparisons with spectroscopic data of literatures.…”
Section: Resultsmentioning
confidence: 99%